Pengaruh Model Pembelajaran Make A Match Terhadap Kemampuan Menulis Teks Eksplanasi Siswa - Besinaria Gea; Rosmawaty Harahap (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This study aims to determine the effect of the Make A Match learning model on the ability to write explanatory texts for class VIII students of SMP Negeri 1 Delitua in the 2022/2023 academic year. The population in this study were all class VIII students of SMP Negeri 1 Delitua, totaling 93 students, divided into 3 class. The sample in this study was class VIII-3 which consisted of 30 students. The method used in this study was an experimental method with a One group pre-test post-test design. . The data analysis technique used in this study is quantitative data by using analysis requirements test, homogeneity test and hypothesis testing. The results showed that the average value of the ability to write explanatory texts before applying the treatment was 53.66 belonging to the less category while the average value of skills to write explanatory texts by applying the treatment was 84.2 belonging to the good category. Based on the t test, a significance level value is obtained with dk = N-1 = 29, so that a ttable value of 2.045 is obtained. Thus it is concluded that tcount > ttable, namely 15.27 > 2.045 so that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This proves that there is a significant effect of using the Make A Match learning model on the ability to write explanatory texts for class VIII students of SMP Negeri 1 Delitua in the 2022/2023 Academic Year.